Yoga for improving mood and cognitive functions - A brief review - Narottam Kumar; Udham Singh (Wolters Kluwer Medknow Publications, 2021)
Generally speaking, people are vulnerable to face rigorous work and learn how to enhance cognitive functions by improving mood state. The extant research evidence appears to support the proposition that yoga may improve mood and cognitive functions of the various populations. Balanced mood state plays a precious role in cognition, quality of life, and successful life. This review highlights the effect of yoga practices on improving mood and cognition and also provides inculcation of various yogic practices as a therapy to improve mood that leads to better cognitive function. It has been found that mood disturbance may lead to poorer cognition and cognitive impairment. Good cognitive functions depend on healthy frontal lobes of the brain and mood states. Therefore, there is need to populate the insights that healthy mood may lead to better cognition as a result of yoga interventions.